The Relationship Nurse Behavior With Ability In Implementing Patient Safety In The Emergency Room Of Prof. Dr. Hi. Aloei Saboe Hospital City Gorontalo - Pipin Yunus; Arifin Umar; Susanti Monoarfa (PSPP JOURNALS, 2022)
Patient safety is very important. The behavior and abilities of nurses play an important role in the implementation of patient safety. This study aims to determine the relationship nurse behavior with the ability in implementing patient safety in the emergency room at Prof. Dr. Hi. Aloe Saboe hospital. The research method uses quantitative analytic observation with a cross sectional design. A sample of 28 respondents was taken with a total sampling technique. Data obtained by observation and analysis of Chi Square test (α = 0.05). The result showed that the behavior of nurses was good is 11 (68.8%) the behavior of nurses were not good is 9 (75%). The results of the analysis test p = 0.024 so it was concluded that there was a relationship between the behavior of nurses and the ability of patient safety in hospitals.